Optimizing the making of written batik on mori cloth automatically using programmed canting motion with temperature and feed rate analysis - Rizal, Akhmad Khoirur; Muzakhim, Azam (Jurnal Polimesin, 2025)
This study aims to optimize the technique of making batik writing on plain cloth using an automatic CNC machine with a regulated temperature and feed rate. Research methods were used. For testing the influence of variation in temperature (70 °C, 80 °C, and 90 °C) and feed rate against the quality of batik pattern and depth penetration of wax. Use of temperature sensors on electric ramps allows precise temperature control at a time-adapted rate, feeding for detection effects on thickness patterns and penetration wax. The result shows that improved temperature wax will increase its penetration in Mori, especially at a low feed rate, which produces a thicker pattern. Rate of displacement or a higher feed rate will speed up the process, but tends to reduce penetration wax and the thickness pattern. At a temperature of 90 °C and a feed rate of 450 mm/min. Quality is optimal for batik patterns and good wax. Balance between temperature wax and rate of displacement or feed rate is important to reach patterned batik results that are deep and consistent, which supports efficient batik production with still guard mark art